Underlying drivers and barriers for solar photovoltaics diffusion: The case of Vietnam. (September 2020) - Do, Thang Nam; Burke, Paul J.; Baldwin, Kenneth G.H.; Nguyen, Chinh The
Abstract: Vietnam experienced a solar photovoltaic (PV) installation boom in the first half of 2019, with installed capacity increasing to 4, 450 MW. This saw Vietnam overtake Thailand to have the largest installed solar PV capacity in Southeast Asia. This paper investigates the underlying drivers of Vietnam's solar boom, barriers to further solar adoption, and suitable strategies for the next stage of solar adoption. Forty-six semi-structured interviews were conducted with experts from government agencies, international organizations, non-governmental organizations, universities, research institutions, and industry. A generous feed-in tariff (FIT) of US$93.5/MWh for new projects, together with supporting policies such as tax exemptions, are found to be the key proximate drivers of Vietnam's solar PV boom. Underlying drivers include the government's desire to enhance energy self-sufficiency and the public's demand for local environmental quality. Limited transmission grid capacity and complex administrative procedures are among the key barriers. Looking forward, Vietnam has substantial potential to continue to scale up solar PV, with market-based mechanisms able to play a large role in this process. Vietnam's case is relevant for broader energy transition discussions. Highlights: Vietnam now has the highest installed solar PV capacity in Southeast Asia. A high feed-in-tariff was a key factor in Vietnam's solar PV boom. Domestic motivations are key underlying drivers. Barriers differ for utility-scale and rooftop solar PV. Substantial opportunities for further solar PV development in Vietnam exist.